2016
DOI: 10.2465/jmps.160312
|View full text |Cite
|
Sign up to set email alerts
|

Cation ordering of {110} and {211} sectors in grandite garnet from Mali

Abstract: The cation ordering of the {110} c and {211} c growth sectors in birefringent garnet from Kayas, Mali was investigated by means of single-crystal X-ray diffraction (SC-XRD) 3d were observed, and crystal structure models for both the {110} c and {211} c sectors should have triclinic symmetry with the space group I 1. The unit-cell parameters of both growth sectors were a = 11.9739(13), b = 11.9742(14), c = 11.9737(13) Å, α = 90.001(9), β = 90.098(9) and γ = 90.014 (10)°for the {110} c sector; a = 11.952(6), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…their returning to the more "regular" positions after constraints were applied ( Supplementary Materials 8 and 13). Also, more or less declinations from the grossular-andradite join are visible at low symmetry grandite samples previously studied by Frank-Kamenetskaya et al (2007), Kobayashi et al (2013), and Nakamura et al (2016); whereas Wildner and Andrut (2001) described declinations from the grossular-uvarovite join of their studied low symmetry uvarovite samples. Shtukenberg et al (2005) found that the difference in sofs should be proportional to the value of angle β 0 in the I 1 space group.…”
Section: B Crystal Structure Refinementsmentioning
confidence: 76%
See 2 more Smart Citations
“…their returning to the more "regular" positions after constraints were applied ( Supplementary Materials 8 and 13). Also, more or less declinations from the grossular-andradite join are visible at low symmetry grandite samples previously studied by Frank-Kamenetskaya et al (2007), Kobayashi et al (2013), and Nakamura et al (2016); whereas Wildner and Andrut (2001) described declinations from the grossular-uvarovite join of their studied low symmetry uvarovite samples. Shtukenberg et al (2005) found that the difference in sofs should be proportional to the value of angle β 0 in the I 1 space group.…”
Section: B Crystal Structure Refinementsmentioning
confidence: 76%
“…(2013), and Nakamura et al . (2016); whereas Wildner and Andrut (2001) described declinations from the grossular–uvarovite join of their studied low symmetry uvarovite samples.
Figure 7.Variations of the Fe 3+ and Al 3+ over the octahedral sites in the , , and Fddd space groups, by average (a) 〈 Y –O〉 and (b) 〈O–O〉 distances.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spe cies of the grossular-an dra dite {Ca 3 }[Al,Fe 3+ ] 2 (Si 3 )O 12 solid-so lu tion bi nary se ries, oc cur ring in a va ri ety of geo log i cal en vi ron ments, are known to ap pear in the form of zoned crystals (Deer et al, 2013;Tanèiae et al, 2012a and ref er ences therein). A sub stan tial num ber of pre vi ously-ob served grossular-an dra dite gar nets ex hibit op ti cal ani so tropy and non-cu bic low sym me try in var i ous space groups, such as: I61 (Takéuchi et al, 1982;Allen and Buseck, 1988;Kingma and Downs, 1989;Frank-Kamenetskaya et al, 2007;Kobayashi et al, 2013;and Nakamura et al, 2016); Fddd (Takéuchi et al, 1982;Gali, 1984;Frank-Kamenetskaya et al, 2007;Badar et al, 2016); Fddd or C2/c (Hirai and Nakazawa, 1986) and R63c or Fddd (Tanèiae et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structures of birefringent ugrandite were reported as orthorhombic structure with the space group Fddd or triclinic structure with the space group I 1 (e.g. Takéuchi et al, 1982;Allen and Buseck, 1988;Wildner and Andrut, 2001;Frank-Kamenetskaya et al, 2007;Kobayashi et al, 2013;Nakamura et al, 2016). Kingma and Downs (1989) examined the crystal structure of iridescent andradite from a skarn deposit in the Sonoma Range, Nevada, USA.…”
Section: Introductionmentioning
confidence: 99%